The fading birth practice: urban Malay mothers in Malaysia negotiating confinement practices. - Syed Hussien, Sh Fatimah Alzahrah (2019)
Malay mothers’ postpartum experiences often include a period of confinement, similar to other Asian parallel practices of “doing the month”. This confinement period comprise of a set of beliefs, rules, and practices based on traditional eastern medicinal knowledge. Cultural practices of postpartum confinement, or berpantang, among urban mothers in Malaysia is competing with modern western medicine in the contemporary setting. The data for this presentation is from a phenomenological study utilising twelve open-ended interviews of couples and two focus group discussions with mothers on their experience of berpantang. Even though it is still widely performed, the elements within berpantang are handpicked by these mothers. According to these mothers, the traditional practices are thought to be inadequate or inferior when compared to the authority of western biomedicine. In events where medical practitioners give opposing advice, all mothers chose to adhere to, and accept biomedicine’s explanations and justifications over the traditional practice. The former cultural figure head, the bidan (midwife), is no longer a part of the birthing process in these urban settings. Urban mothers today rely on or refer to their maternal mothers for knowledge and guidance on berpantang. Urban mothers who practise berpantang describe the main reason for their practise was to maintain familial peace. This paper seeks to highlight social and cultural implications this hegemony has particularly on challenging the continuity in the chain of traditional knowledge.